KCNJ11 gene expression is associated to feed consumption and growth traits in Nelore beef cattle - Diniz, Wellison J.S.; Rosa, Kamila O. [UNESP]; Coutinho, Luiz L.; Tizioto, Polyana C.; de Oliveira, Priscila S.N.; de Souza, Marcela M.; Chaves, Amália S.; Lanna, Dante P.D.; Mourão, Gerson B.; Regitano, Luciana C.A. (Elsevier, 2018)
Feed efficiency is a complex trait influenced by several genes and biological processes. However, there is limited knowledge about the genes and pathways involved in this trait. KCNJ11, related to the insulin secretion pathway, was shown to be a functional candidate gene for beef quality traits in Nelore. Given its role in energy metabolism, we evaluated the effects of KCNJ11 gene expression level on feed efficiency-related, carcass and growth traits in Nelore steers. Skeletal muscle KCNJ11 mRNA levels were positively and significantly associated with dry matter intake (DMI), total digestible nutrients consumption (TDN), average daily gain (ADG), and relative growth rate (RGR) from a general linear mixed model approach. Co-expression analysis, using RNA sequencing data obtained from Longissimus dorsi (LD) muscle of 30 Nelore steers, identified key signalling pathways related to the regulation of energy metabolisms, such as mitogen-activated protein kinases and insulin pathways. Our findings indicate a linear relationship between KCNJ11 gene expression and the phenotypic measures for feed intake, weight gain, and relative growth rate in Nelore steers, but not for residual feed intake or fat deposition traits.
Keywords: Average daily gain; Dry matter intake; Insulin pathway; Relative growth rate; Total digestible nutrients consumption